The End of the Partnership With a Guide Dog: Emotional Responses, Effects on Quality of Life and Relationships With Subsequent Dogs - Lloyd, Janice; Budge, Claire; La Grow, Steve; Stafford, Kevin (Frontiers in Veterinary Science, 2021)
Guide dogs are mobility aids which facilitate independent travel of people who are blind or visually impaired. Additional benefits imparted to the guide dog handler include companionship, and increased: social-function, self-esteem and confidence. Some evidence shows that the end of the guide dog partnership can result in reduced mobility, and may have profound psychosocial effects on the handler due to feelings of bereavement and loss of self-esteem. However, this evidence is limited. This study examined the experiences and feelings of 50 people across New Zealand, who have used one or more dogs as guides (118 pairings), to explore issues arising at the end of the partnership and how this may impact on relationships with subsequent dogs. Results indicate that the majority of handlers experienced a reduction in their quality of life due to a decrease in independent mobility followed by the loss of a friend and companion, and curtailment of social interactions. Feelings at the end of the partnership affected the handlers’ relationships with subsequent guide dogs in different ways, with around a third expressing a negative effect. Retiring a guide dog (for whatever reason) is not only difficult for the handler, but also for the handler’s family, friends, co-workers, and doubtlessly, the dog. The majority of handlers expressed feelings of extreme grief (including anger and guilt) when the partnership ended, whether it was successful or not. The depth of emotion was compared to losing a family member or other loved one, which has been reported in some person and pet relationships. Feelings of extreme grief were more common for first than second dogs. Distress caused by the end of the partnership between a handler and a guide dog might be more intense than that experienced between a person and a pet because the dog helps the handler to do things that could not be accomplished alone; this should be addressed in any assistance dog program. A better understanding of the end of the partnership will help inform the guide dog industry of how best to support their clients during this time and when transitioning to another dog.